"I Do Belong Here": Identity Perceptions of Postgraduate Music Education Majors. Issue 1 (October 2019) - Sieger, Crystal
Students choosing to enter the music teaching profession after having already obtained undergraduate degrees in other music fields may experience unique forms of socialization and teacher identity development. Participants were four students enrolled in a 3-year master's program with a music teacher licensure component. Through individual and focus group interviews, participants shared their perspectives on program experiences, course elements, and interactions with peers and professors as important influences on their developing music teacher identity. I examined the data for emerging patterns and applied open and axial coding to the most prominent responses, resulting in themes centered on participants' socialization experiences, desire for independence, need for self-justification, and "outsider" status among peers. To combat lack of peer recognition or support, participants developed strong, collaborative relations with each other. Implications for music teacher educators are considered.